(untitled) (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT Taking into consideration folkcommunication, folkmarketing and folkgastronomy, this work thematizes the representations of traditional identities of cuisine and northeastern culture in globalized scenarios through the franchise of Brasil Vexado. The main purpose of our research is to answer the question: What processes developed by the brand allowed to use traditional identities of culinary and northeastern culture in the scenario of the globalized world? The objective is to clarify the cultural and dynamic negotiations of the processes of cultural hybridization that mark the relationship of the masses with popular gastronomic environment. To accomplish this goal, we performed the data analysis of the market strategies and practices of the Brazil Vexado franchising network, aiming to show the relationships that the brand has established between the cultural heritage and its related identities. KEY-WORDS Folk-communication; North eastern culture; Fast Food; Brasil Vexado.